2014
DOI: 10.1161/atvbaha.114.303644
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small Proline-Rich Repeat Protein 3 as a Novel Atheroprotective Factor That Promotes Adaptive Akt Signaling in Vascular Smooth Muscle Cells

Abstract: Objective Atherosclerosis is the primary driver of cardiovascular disease, the leading cause of death worldwide. Identification of naturally occurring atheroprotective genes has become a major goal for development of interventions that will limit atheroma progression and associated adverse events. To this end, we have identified SPRR3 (small proline-rich repeat protein 3) as selectively upregulated in vascular smooth muscle cells (VSMCs) of atheroma-bearing arterial tissue versus healthy arterial tissue. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…We previously reported that regulation of type I collagen transcript levels by Sprr3 may be PI3K/Akt dependent 20,21 . Other studies have also shown that Akt signaling can modulate type I collagen levels in various cell types 28‐30 .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…We previously reported that regulation of type I collagen transcript levels by Sprr3 may be PI3K/Akt dependent 20,21 . Other studies have also shown that Akt signaling can modulate type I collagen levels in various cell types 28‐30 .…”
Section: Resultsmentioning
confidence: 95%
“…Nonepithelial expression of several members, such as SPRR3 and SPRR2a, have been recently reported, yet their cellular and mechanistic roles are unclear 22,23 . Our group discovered high expression of SPRR3 in atheromatous plaques of larger arteries where its expression is restricted to vascular smooth muscle cells 20,21 . In response to mechanical stress, SPRR3 upregulates type I collagen expression in VSMCs, augments proliferation, and enhances basal phosphorylation of Akt and p38 19,20 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…93 Genetic deficiency of SPRR3 augmented atherosclerosis in apoE −/− mice, which were attributed to regulation of Akt signaling in SMCs. 94 Therefore, roles of SMC survival and apoptosis in the development of atherosclerosis through Akt signaling pathway have not been consistent in the literature.…”
Section: Resident Cell Types In Atherosclerosismentioning
confidence: 97%